Pendidikan Kesehatan Pencegahan Kegawatdaruratan Kehamilan Unsafe Abortion pada Remaja - Ulaa, Mar'atun; Marlin, Rizka; Azmi, Khusnul Tisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of educational videos on teenagers' knowledge about unsafe abortion. The method used was a quasi-experiment with a nonequivalent pretest-posttest non-control group design, which was carried out in July 2022 at IKesT Muhammdiyah Palembang with a sample of 65 people who were given health education about preventing pregnancy emergencies. The results of the research show that statistically, health education can avoid emergencies of pregnancy; unsafe abortion in adolescents is effective in increasing respondents' knowledge with a p-value of 0.000. Conclusion: Educational videos can increase teenagers' knowledge about unsafe abortion Keywords: Video Education, Pregnancy Emergency, Adolescents, Unsafe Abortion